Meningkatkan Kemampuan Public Speaking Siswa melalui Media Wayang Kertas - Panjaitan, Chery Julida; Wahidah; Soraya, Dara; Adelia, Magfirah; Syahputri, Resti Restari; Ulhusna, Risna; Siregar, Nurul Huda; Masyitah, Nur (LSM Catimore dan Sahabat, 2024)
This research aims to improve students' public speaking skills through Wayang Kertas media. This research used an experimental method consisting of 6 meetings. The 6 meetings included 2 observations and 4 public speaking teaching sessions through Wayang Kertas media. Researchers conducted research in Sidodadi Village, Langsa City with a total of 7 students. Based on research results, the use of paper puppet media can improve students' public speaking skills in elementary schools. This innovative and engaging approach not only improves students' public speaking skills, but also provides space for them to be more actively involved in the learning process, enriching their learning experience and stimulating creativity. These results show that creative and innovative learning approaches, such as the use of paper puppets, improve communication skills at the basic education level.